Effect of Preoperative Nebulized Ketamine on Incidence and Severity of Postoperative Sore Throat in Patient Undergoing General Anaesthesia with Endotracheal Intubation - Bhatta, Prajjwol D; Shakya, Bigen M; Bista, Navindra R; Marhatta, Moda N; Shrestha, Ninadini (Journal of Institute of Medicine Nepal, 2020)
Introduction Postoperative sore throat (POST) has a reported incidence of up to 62% following general anaesthesia. POST was rated by patients as the eighth most undesirable outcome in the postoperative period. The objective of this study was to compare the incidence and severity of postoperative sore throat after saline and ketamine nebulization in patients undergoing general anaesthesia with endotracheal intubation. Methods The study was prospective double blinded randomized controlled trial . One hundred patients belonging to American Society of Anesthesiologists physical status I–II undergoing surgery under general anaesthesia with endotracheal intubation were randomized into two groups; group Saline (S) received nebulization with 5 ml of normal saline and group Ketamine (K) received nebulization with 1 ml of ketamine of concentration 50 mg/ml mixed with 4 ml saline. POST was assessed at zero hour, two hour, four hour, six hour, eight hour and 24 hour. Results The overall incidence of POST was 28%. Twenty two (44%) patients in group S and six (12%) patients in group K had postoperative sore throat at some point of the study. The POST was significantly reduced in group K at zero hour 3(6%), two hour 3(6%), four hour 4(8%), six hour 5(10%) and eight hour 3(6%) with p value <0.05 . The severity of POST was also significantly decreased in group K at zero hour, two hour, four hour, six hour, eight hour with p value <0.05. Conclusion Preoperative nebulization with ketamine reduces the incidence and severity of POST after general anaesthesia with endotracheal intubation.